Brain and Mind Integration: Childhood Sexual Abuse Survivors Experiencing Hyperbaric Oxygen Treatment and Psychotherapy Concurrently - Lev-Wiesel, Rachel; Bechor, Yair; Daphna-Tekoah, Shir; Hadanny, Amir; Efrati, Shai (Frontiers in Psychology, 2018)
Due to evidence that traumatic experience impacts the brain, the body (concerning sensory sensitivity), and the mind, a recent study that attempted to answer the question of whether the effects of CSA can be reversed by using a multidisciplinary approach consisting of dual treatments: hyperbaric & psychotherapy, was conducted. Its results showed that in addition to improvement of brain functionality, symptoms of distress were significantly reduced. The current paper aims to present the process as experienced by the 40 female childhood sexual abuse survivor participants. Data included participants’ daily journals and drawings, and participants’ summaries presented verbally and written, 6-months after the study ended. A phenomenological analysis was used. Results showed three phases, the initial phase – remembering the trauma from both physical and cognitive aspects, the second phase - physiological relaxation as well as positive memories emerge; and, the third phase – bouncing back to life. The results are discussed in light of the study theoretical model and Lev-Wiesel (2014) childhood sexual abuse conceptualization.